Tracing the iron nitrosyl complex [Fe(2,2-bipyridine)(CN)3(NO)]- - Foi, Maria Ana (2015)
The previously reported complex [Ph4P][Fe(bpy)(CN)3(NO)] (bpy = 2,2-bipyridine) was synthesised and characterised in detail using UV/Vis absorption and IR spectroscopy, cyclic voltammetry, and single-crystal XRD. Detailed spectroelectrochemical (UV/Vis, IR and EPR) insight adds perfectly to the previous electrochemical characterisation of this complex. The description of this {Fe(NO)}7 complex as a low-spin FeII-NO· system based on the spectroscopic results is supported by DFT calculations. Reversible oxidation leads to the corresponding {Fe(NO)}6 (FeII-NO+) complex, whereas the reduction to the formal {Fe(NO)}8 species [presumably (FeII-NO-)] occurs irreversibly. When trying to synthesise further derivatives that contain other α-diimine ligands, only for the 1,10-phenanthroline (phen) derivative were some results obtained. For other ligands the obtained materials were too reactive. The reasons for such behaviour are also discussed.